Pioneumoquiste y abscesos miliares de hígado - Rossi, Rodolfo (1937)
The authors relate the case of a young woman with antecedent history of hepatic colics which presented as hydatic choledoch syndrome, with acholia and bile pigments in tin* urine, remittent fever, jaundice and internal enlargement of the liver. Next, consisted of : Finding of hydatid cysts in the vomits, and fecal matter, with eosinophilia and positive Cassoni and Ghedini tests. Radiographic and radiological control showed a subdiaphragmatic area consisting of liquid and air. The general condition of the patient was very bad. The succesive interventions demonstrated a multilocular cyst containing pus and air in the super-external area, with miliary abscess in the liver. The patient died in a month.